Penekanan Pemahaman Pulsa Pada Materi Ajar Drums 1 Yamaha Music Foundation - Aryuda Fakhleri Fallen; Agung Dwi Putra (FBS Universitas Negeri Padang, 2020)
This study aims to find out how the emphasizing is on pulses understanding in the Drums 1 Yamaha Music Foundation teaching material. The type of this research is a qualitative paradigm with a content analysis approach. The object of this research was the Drums 1 Yamaha Music Foundation book, and the research subject was pulse suppression contained in the drum practice material. The research instrument was the author itself and was assisted by supporting instruments such as stationery, laptop, and mobile phone. The data were collected through observation, interview, and documentation. The data types were primary and secondary data. The data were analyzed through practicing, analyzing, eliciting findings, describing findings, and making conclusion. The results show that the Drums 1 Yamaha Music Foundation book is a teaching material intended for students / drummers at the beginner stage (beginner) in the 10th & 9th grade. Therefore, Yamaha provides systematic learning and focuses on pulses as a reference for learning, so pulses are considered crucial. This study reveals the pulses implicitly stated in the Drums 1 Yamaha Music Foundation book where pulses are implemented in 3 forms of practice patterns which are mutually applied. The quarter pulses applied to stick control is a main foundation to orchestrate the pulses in the from of not subdivision, not variation, rhythm pattern, and the drum fill-in. The difference is on where the focus is located. So the research definitively has proven that there is emphasizing of pulses which are presented in various forms of practice patterns.